2007
DOI: 10.1111/j.1365-2265.2007.02743.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of resistin plasma levels in subjects undergoing coronary angiography

Abstract: Resistin plasma concentrations are related to inflammatory processes and renal function but our study does not support the hypothesis of resistin as an independent cardiovascular risk factor. The unexpected association of resistin with noncardiovascular mortality still warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 38 publications
2
41
0
1
Order By: Relevance
“…In contrast, no relationship between Resistin levels and CAD was found among 1161 subjects in the LU-RIC study [113] . Moreover, Resistin was not associated with cardiovascular mortality.…”
Section: Resistinmentioning
confidence: 76%
“…In contrast, no relationship between Resistin levels and CAD was found among 1161 subjects in the LU-RIC study [113] . Moreover, Resistin was not associated with cardiovascular mortality.…”
Section: Resistinmentioning
confidence: 76%
“…High resistin level appears to be associated with poor outcome after atherothrombotic ischemic stroke, independently of other adverse predictors (Efstathiou et al, 2007). However, some studies have not detected an association between elevated circulating resistin level and either prevalence or outcome of CAD (Yaturu et al, 2006;Hoefle et al, 2007;Pilz et al, 2007;Piestrzeniewicz et al, 2008). The discrepancy between study results could be related to differing demographics of the study groups, study design and patient selection criteria and also to non-standardized assay method.…”
Section: Human Resistin In Atherosclerosis and Coronary Artery Diseasementioning
confidence: 99%
“…In contrast, several other studies (29,30) found that resistin levels are higher in different cardiovascular conditions. More important, the same Pilz et al (28) found an increase in mortality in hyperresistinemic patients, and Lubos et al (31) demonstrated that resistin levels predict cardiovascular mortality in patients with coronary artery disease. Our study found a mechanism through which resistin can affect cardiovascular physiology and contribute to human disease, thus extending recent observations (32) showing that vascular cells are a target of resistin also independently of metabolic effects.…”
Section: Discussionmentioning
confidence: 92%
“…On this note, epidemiological studies so far have been inconclusive. A recent study (27) did not find an association between resistin levels and cardiovascular events in Korean diabetic patients, and Pilz et al (28) related resistin levels to inflammatory processes and renal function but not to the incidence of some cardiovascular diseases. In contrast, several other studies (29,30) found that resistin levels are higher in different cardiovascular conditions.…”
Section: Discussionmentioning
confidence: 99%